2022
DOI: 10.1111/geb.13492
|View full text |Cite
|
Sign up to set email alerts
|

Soil macroinvertebrate communities: A world‐wide assessment

Abstract: Aim: Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed worldwide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices.Location: Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 50 publications
6
34
0
Order By: Relevance
“…Identifying soil macro-invertebrates to a higher taxonomic resolution is time-consuming and needs taxonomic expertise for many different groups 24 . Therefore, a low taxonomic resolution has been the norm in soil ecological and zoological research for a long time and it has been shown to be sufficient to identify general patterns for entire communites [24][25][26][27] or individual taxa 28 . Commonly used biodiversity indices such as the QBS index 29 or the IBQS index 30 work with low taxonomic resolution.…”
Section: Background and Summarymentioning
confidence: 99%
“…Identifying soil macro-invertebrates to a higher taxonomic resolution is time-consuming and needs taxonomic expertise for many different groups 24 . Therefore, a low taxonomic resolution has been the norm in soil ecological and zoological research for a long time and it has been shown to be sufficient to identify general patterns for entire communites [24][25][26][27] or individual taxa 28 . Commonly used biodiversity indices such as the QBS index 29 or the IBQS index 30 work with low taxonomic resolution.…”
Section: Background and Summarymentioning
confidence: 99%
“…Table 1 gives a detailed list of soil fauna functional groups considered in this study. Despite significant progress in research focused on soil fauna, the interrelated functional roles of various groups of soil fauna remain poorly understood 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The global distribution of soil fauna and their consumption of litter is interpreted to depend on a set of hierarchical factors like climate, soil properties, and vegetation, which are often themselves interrelated 19 , 24 , 28 , 42 . Climate modifies litter decomposition indirectly via its effects on vegetation, soil type, and soil organismic communities 19 , 28 , 43 , 44 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent initiatives produced global data sets that represent the distribution of soil microbial diversity (Aslani et al, 2022; Bahram et al, 2018b, 2022; Delgado‐Baquerizo et al, 2018; Egidi et al, 2019; Maestre et al, 2015; Tedersoo et al, 2014). Other initiatives compiled already existing data on the abundance and diversity of soil animals (van den Hoogen et al, 2019; Lavelle et al, 2022; Phillips et al, 2019; Potapov, 2022), soil microbial biomass (Patoine et al, 2022; Xu et al, 2013), fungal communities ( GlobalFungi ) and guilds (FungalTraits; Põlme et al, 2020), and plant mycorrhization types (FungalRoot; Barceló et al, 2019; Soudzilovskaia et al, 2020). This opens exciting opportunities for data integration for a holistic description of the soil biosphere.…”
Section: Frontiers In Soil Ecologymentioning
confidence: 99%